Unmasking the Illusion: The Tech Behind Deepfakes - Brienza, Michele; Bloisi, Domenico Daniele; Nardi, Daniele (Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project, 2026)
The chapter provides an overview of the technology behind deepfakes, describing what a deepfake is and how it is created. The chapter is structured around three sections: (i) theoretical foundations of artificial intelligence, machine learning, and deep learning, (ii) generative models and synthetic data, and (iii) the synthetic media toolkit. Firstly, it describes AI evolution, starting from the early stages leading up to the latest models that can generate data. The latest models are then described, highlighting their capabilities and explaining how these models open a wide range of opportunities, as well as the concerns regarding the generation of highly realistic data that can deceive users, as is the case with deepfakes. Finally, knowledge of how the machines learn from the data helps in using these tools. A clear understanding of the process behind the technology leads to unmasking the illusion and understanding how the technology works, enabling informed use.